PENGGUNAAN MEDIA SEDERHANA PADA PEMBELAJARAN MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Fazira, Dela; Yennita, Y; Irianti, Mitri (LPPM UNIVERSITAS PGRI SILAMPARI, 2024)
This research aims to determine the differences in student learning outcomes who apply learning using simple media and conventional learning on dynamic electrical material. This research uses a quasi-experimental design, with a posttest-only control group design. The sample in this research were students from Brawijaya I and Brawijaya II IX classes at Taruna Sakti Middle School. Multiple choice questions with a total of 18 questions were the data collection method used in this research. In carrying out descriptive analysis, data analysis methods include analysis of calculating the mean, median, mode, and standard deviation. Student learning outcomes in classes that use simple media show a high category with an average of 74.95, while classes that take part in conventional learning reach the sufficient category with an average of 63.38. Thus, it shows that there are differences in the learning outcomes of students who apply learning using simple media and those who apply conventional learning.